Cinética de la generación del petróleo: principios y aplicación en las cuencas Colombianas - T. Goncálvez, F. T.; García, D. F.; B. Penteado, H. L.; Giraldo, B. N.; Bedregal, R. P.; Gómez, P. (CT&F - Ciencia, Tecnología y Futuro, 2001)
Most of the mathematical models that describe the conversion of kerogen into petroleum are based on the formulations of first-order kinetics. Although the application of such models requires the knowledge of the kinetic parameters (activation energies and frequency factor) of the kerogen, the usual practice in basin modeling studies is to use kinetic data of standard kerogen types (I. II or III) when measured data are not available. In this study, Rock-Eval pyrolysis under different heating rates and numerical optimization techniques were used to determine the kinetic parameters of Cretaceous and Tertiary source rocks of the Upper Magdalena and Llanos basins. The obtained kinetic parameters revealed a significant variability, which appears to be unrelated to the kerogen type classification based on hydrogen and oxygen indices Modeling exercises under a constant heating rate (1.25°C/M.y., 274.5K/M.y.) using the measured kinetic data indicates that kerogen conversion of organic facies with distinct kinetic parameters may be out of phase by 20-30M.y. Therefore. petroleum generation and expulsion history might be longer and more complex than if the kinetic behavior of these rocks was considered homogeneous. These differences are critical in defining the timing between petroleum generation an trap formation/destruction, particularly in the case of the Colombian sedimentary basins, characterized by a highly complex tectonic evolution.